2004
DOI: 10.1104/pp.103.031088
|View full text |Cite
|
Sign up to set email alerts
|

Transient Exposure to Ethylene Stimulates Cell Division and Alters the Fate and Polarity of Hypocotyl Epidermal Cells

Abstract: After transient exposure to the gaseous hormone ethylene, dark-grown cucumber (Cucumis sativus) hypocotyls developed unusual features. Upon ethylene's removal, the developing epidermis showed significant increases in cell division rates, producing an abundance of guard cells and trichomes. These responses to ethylene depended on the stage of development at the time of ethylene exposure. In the upper region of the hypocotyl, where cells were least differentiated at the onset of ethylene treatment, complex, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 44 publications
0
49
0
2
Order By: Relevance
“…The inhibition of this response in trees where ethylene perception was reduced (transgenic and 1-MCP-treated wild type) further showed that it was mediated through ethylene receptors. Application experiments have also demonstrated a potential for ethylene to stimulate endoreduplication in hypocotyls of Arabidopsis and cucumber (11)(12)(13), cell division activity, and the induction of cell cyclerelated genes in adventitious root formation and in the intercalary meristem of deepwater rice (25,26). In line with these observations, overproduction of ethylene in Arabidopsis roots due to the loss of function of ETO1 [encoding a BTB/POZ protein that regulates ACS5 stability, and hence elevated ethylene biosynthesis, through ubiquitin E3 ligase complex (27)] not only inhibited root elongation but also induced additional cell division in the quiescent center, and a function for endogenous ethylene in postembryonic stem cell division was postulated (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of this response in trees where ethylene perception was reduced (transgenic and 1-MCP-treated wild type) further showed that it was mediated through ethylene receptors. Application experiments have also demonstrated a potential for ethylene to stimulate endoreduplication in hypocotyls of Arabidopsis and cucumber (11)(12)(13), cell division activity, and the induction of cell cyclerelated genes in adventitious root formation and in the intercalary meristem of deepwater rice (25,26). In line with these observations, overproduction of ethylene in Arabidopsis roots due to the loss of function of ETO1 [encoding a BTB/POZ protein that regulates ACS5 stability, and hence elevated ethylene biosynthesis, through ubiquitin E3 ligase complex (27)] not only inhibited root elongation but also induced additional cell division in the quiescent center, and a function for endogenous ethylene in postembryonic stem cell division was postulated (14).…”
Section: Discussionmentioning
confidence: 99%
“…Additional observations also support a potential role for ethylene in cell division. Applied ethylene stimulated endoreduplication in cucumber hypocotyls and growth of the intercalary meristem in deepwater rice (11)(12)(13). Moreover, the ethylene-overproducing Arabidopsis mutant eto1 exhibits aberrant cell divisions in the quiescent center of the root (14).…”
mentioning
confidence: 99%
“…Light-grown plants, on the other hand, show limited longitudinal shoot growth, rapidly forming short and round pseudobulbs and normal green leaves (Suzuki and Kerbauy, 1999). Several effects of ethylene on shoot growth (Cary et al, 1995), cell division (Kazama et al, 2004) and hormone levels (Peres et al, 1999) have been reported. Up to now, experiments conducted to explore plant growth and development controlled by internal cues, such as hormonal balance, and by external factors have not, unfortunately, yielded conclusive information.…”
Section: Introductionmentioning
confidence: 99%
“…For example, auxin can suppress cytokinin biosynthesis (Nordströ m et al, 2004), auxin and cytokinin can act synergistically to induce ethylene biosynthesis (Vogel et al, 1998), and ethylene can modify auxin responses and meristem function (Morgan and Gausman, 1966;Suttle, 1988;Visser et al, 1996;Haver et al, 2002;Vandenbussche et al, 2003;Souter et al, 2004;Stepanova et al, 2005). Depending on the exposure, ethylene can either inhibit or promote cell division and influence cell fate (Kazama et al, 2004), and in part it acts through interactions with DELLA proteins (Achard et al, 2003). The roles of actin and tubulin components are also receiving much attention, both as being modified by hormones and signaling pathways (Lang et al, 1982;Cyr, 1991;Lloyd et al, 1996;Gardiner et al, 2001;Hussey, 2004) and as themselves being implicated as regulators of hormonal signaling systems (Geldner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%